2014
DOI: 10.1007/s10529-014-1458-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in use of 1-aminocyclopropane-1-carboxylate (ACC) deaminase for conferring tolerance to biotic and abiotic stress

Abstract: Ethylene is an essential plant hormone also known as a stress hormone because its synthesis is accelerated by induction of a variety of biotic and abiotic stress. The plant growth promoting bacteria containing the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase enhances plant growth by decreasing plant ethylene levels under stress conditions. The expression of ACC deaminase (acdS) gene in transgenic plants is an alternative approach to overcome the ethylene-induced stress. Several transgenic plants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 46 publications
1
36
0
1
Order By: Relevance
“…This phenomenon was, however, demonstrated for PGPR (Dashti et al 1998;Chebotar et al 2001;Valverde et al 2006;Figueiredo et al 2008;Yadegari et al 2010) and some mechanisms whereby these bacteria affect BNF were described previously. For instance, the production of IAA and ACC deaminase by PGPR is known to increase nodule ATP and longevity respectively (Takahashi et al 2012;Gontia-Mishra et al 2014). Considering that during the present study we found that C. laurentii CAB 91 was able to produce IAA and ACC deaminase in vitro, it seems possible that this yeast influenced the BNF of CL treated plants in a similar manner than PGPR.…”
Section: Discussionsupporting
confidence: 50%
“…This phenomenon was, however, demonstrated for PGPR (Dashti et al 1998;Chebotar et al 2001;Valverde et al 2006;Figueiredo et al 2008;Yadegari et al 2010) and some mechanisms whereby these bacteria affect BNF were described previously. For instance, the production of IAA and ACC deaminase by PGPR is known to increase nodule ATP and longevity respectively (Takahashi et al 2012;Gontia-Mishra et al 2014). Considering that during the present study we found that C. laurentii CAB 91 was able to produce IAA and ACC deaminase in vitro, it seems possible that this yeast influenced the BNF of CL treated plants in a similar manner than PGPR.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have demonstrated the beneficial effects exerted by PGP bacteria on the laboratory scale (Bhardwaj et al 2014;Gontia-Mishra et al 2014;Daffonchio et al 2015;Haney et al 2015), but relatively less data are available under on the field scale (Bashan et al 2014 and references therein;Nelissen et al 2014). Translating laboratory results to field trials is important for the future development of crop productivity (Tuberosa 2012;Bashan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of 1-aminocyclopropane-1-carboxylate (ACC) deaminase (which catalyzes the hydrolytic cleavage of ACC, the immediate precursor of ethylene, and is therefore an inhibitor of ethylene biosynthesis) in EI than in control leaves (Table S-2) is another indication that S. oryzae infestation interfere with ethylene biosynthesis. Several transgenic plants have been engineered to express the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase in order to decrease plant ethylene levels and enhance tolerance to biotic and abiotic stresses 104 . Probably as a consequence of ACC deaminase activity (which results in low ACC levels for ethylene biosynthesis), we detected higher expression of three ACC oxidase genes ( OsACO3 , 5 and 7 ) in rice leaves infested with S. oryzae , when compared to control leaves (Figure 6e–g).…”
Section: Resultsmentioning
confidence: 99%